(untitled) (Research, Society and Development, 2021)
Introduction: biofilm is a culture of sessile bacteria, isolated from the external world, capable of internal communication and signalization, which allow for the development of phenotypic changes to adapt to hostile environments. Given its easy pathogenic dissemination, biofilms can develop in prosthetics and implantable medical devices, forming focal nosocomial infections. Objective: to comprehend biofilm formation mechanisms in implantable cardiac devices in an intra-hospital environment, as well as the treatment and prophylactic measures to treat this condition. Materials and methods: descriptive and observational exploratory study based on a literary review on biofilm formation, its consequences in a hospital environment, and infections caused by proliferation on implantable cardiac devices. In total, 28 articles were selected using the following descriptors: ((nosocomial) AND (cardiac)) AND (devices). Results: biofilm grows in an uneven form, being influenced by strain and environment. It has a high virulence when it comes to growing on implantable cardiac devices considering its ability to adhere to biotic and abiotic surfaces. Immunosuppression and the lack of surgical sterilization are factors that can contribute to complications associated with the use of these devices, such as infectious endocarditis. Conclusion: biofilm, due to its pathogenicity and virulence, is a serious though rare complication in patients that use implantable devices. There is evidence that contamination occurs mainly in surgical environments, making it necessary the application of more rigorous sterilization techniques.